THE INFLUENCE OF INTERNAL AND EXTERNAL FACTORS OF RED PLANT BANKING COMPANIES ON SHARE PRICES FOR THE 2010 - Enny Istanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Bank Indonesia stated that the global economy continues to experience a decline in line with the impact of the crisis in developed countries which has begun to be felt by emerging market countries. Ratio) to stock prices and how much influence external factors (Inflation & Interest Rates) have on stock prices. The research method used in this research is to use the Multiple Linear Regression Analysis approach. The conclusion obtained in this study is that the Return on Assets and Capital Adequacy Ratio partially have a significant influence on the stock price of Government Banking, while the Loan to Deposit Ratio, inflation and interest rates partially have no significant effect on the share price of Government Banking. Loan to Deposit Ratio, Return On Assets, Capital Adequacy Ratio, inflation and interest rates together have a significant influence on the stock price of Red Plate Banking. The variable that has a significant dominant influence on the stock price of Red Plate Banking is Return On Assets, with an influence value of 47.06%.